A study regarding student satisfaction on medical graduate license examinations and career guiding sessions around the globe including the NEXT (National Exit Test) exam of India using qualitative and quantitative methods in a medical college of North - Bhanupriya Shivshankar Pande; Amit Jagannath Patil; Aashutosh Ramakant Patel; Dnyaneshwari Pande,; Vaishnavi Galande; Rohit Garde, (Global Journal of Medicine and Public Health)
Context:The National Medical Commission of India in the year 2019 recommended the National level licenses exam